Yield and yield components of certain Hevea clones at higher elevation - Reju M J; Arun Kumar K; Deka H K; Thapliyal A P; Varghese Y A (Placrosym XIII, 1998, Coimbatore, Tamil Nadu, India. Recent Advances in Plantation Crops Research, p138-143, 1998)
A non-traditional area of Garo hills, Meghalaya has been identified as one of the potential areas for extension of rubber cultivation. A study was conducted to evaluate the performance of seven clones of Hevea brasiliensis under the agroclimatic conditions of Tura. Data on girth increment (GI), dry rubber yield (RY), plugging index (PI), dry rubber content (DRC), soil moisture (SM) and all relevant agrometeorological parameters were correlated with each other. Among the seven clones, RRIM 600 recorded highest dry rubber yield (26.4g/tree/tap) over the first three years of tapping followed by RRII 118 and RRII 105. However, variation in dry rubber yield was not significant. Although RRII 105 the highest yielding clone in the traditional region does not top the list with respect to the yield pattern in this region. GI, RY, and SM had a positive correlation while PI showed negative correlation with RY.
Keywords: Hevea clone; Yield